2014
DOI: 10.1021/es502174p
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Aggregation and Surface Deposition Processes of Engineered Superparamagnetic Iron Oxide Nanoparticles for Environmental Applications

Abstract: Engineered, superparamagnetic, iron oxide nanoparticles (IONPs) have significant potential as platform materials for environmental sensing, imaging and remediation due to their unique size, physicochemical and magnetic properties. To this end, controlling the size and surface chemistry of the materials is crucial for such applications in the aqueous phase, and in particular, for porous matrixes with particle-surface interaction considerations. In this study, superparamagnetic, highly monodispersed 8 nm IONPs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 71 publications
5
78
0
Order By: Relevance
“…For Al 13 and Al 30 , with direct inspection, the slope of ΔD to Δf exhibited a linear relationship, which meant that no conformational alternation occurred during the deposition process (Che et al, 2014). With respect to Al o , the slope became larger with increasing | Δf | , which meant that the film became more loosely attached to the surface (Li et al, 2014).…”
Section: Deposited Layer Characteristicsmentioning
confidence: 97%
See 1 more Smart Citation
“…For Al 13 and Al 30 , with direct inspection, the slope of ΔD to Δf exhibited a linear relationship, which meant that no conformational alternation occurred during the deposition process (Che et al, 2014). With respect to Al o , the slope became larger with increasing | Δf | , which meant that the film became more loosely attached to the surface (Li et al, 2014).…”
Section: Deposited Layer Characteristicsmentioning
confidence: 97%
“…The viscoelastic properties and conformational changes of the deposited layers could be evaluated by the ΔD-Δf plot, as shown in Fig.7a (Li et al, 2014). The slope of ΔD to Δf was steepest with Al o , followed by Al 30 and Al 13 , which indicated that the deposited layer of Al 13 was the most rigid and a most soft dissipative film was formed for Al o .…”
Section: Deposited Layer Characteristicsmentioning
confidence: 99%
“…Such strategies are used in oil-field rocks and contaminated geological systems. [7] Many technical applications are based on ferrofluids, which consist of magnetic nanoparticles in a non-magnetic solvent. Examples are damping devices or magnetic seals for rotating shafts.…”
Section: Applications Of Magnetic Iron Oxide Nanoparticlesmentioning
confidence: 99%
“…Meanwhile, the hydrophobicity of QCM-D sensor plays an important role in controlling the nanoparticle deposition. The deposition of OA-IONPs on polystyrene-coated sensor surfaces, on the other hand is stronger than on hydrophilic silica sensor surfaces as a result of increasing surface hydrophobicity as compared withunmodified silica sensor surfaces [136]. These results cannot be adequately described by the classic DLVO theory.…”
mentioning
confidence: 92%